APORTES PARA UNA EPIDEMIOLOGÍA DEL SUICIDIO EN COSTA RICA: UN ANÁLISIS DE LA PRIMERA DÉCADA DEL SIGLO XXI - Sáenz Rojas, Mario A. (Universidad de Costa Rica, 2012)
This article presents statistical data regarding the suicidal epidemiology in Costa Rica, during the years 2000-2009. The information is divided into four categories for its thorough understanding and analysis, establishing as far as possible, comparisons with what has happened in other countries: dimension of the phenomenon, frequency of the phenomenon, gender and location. Finally, it presents a discussion on prevention and the need of a mental health policy, investigation to deepen the knowledge on this area and the urgency of work in the axis of masculinity and violence